The Character Development of Neville Longbottom in the Harry Potter Series - Alvanita Alvanita (Lexicon, 2012)
This graduating paper examines the novel series Harry Potter by J.K. Rowling. There are seven series telling about the journey of Harry Potter in Hogwarts school of witchcraft and wizardry. The objectives of this paper are to study the character development of Neville Longbottom, a minor character in Harry Potter, and to find his significance in the Harry Potter series. The analysis is conducted with objective approach, focused on changes in Neville’s character. The result of this research shows that Neville character changes significantly during the series. Moreover, his development becomes very significant to the plot of Harry Potter. At first, he is obedient and shy, but finally in the end of series he becomes a hero. He is a minor character, yet he has a significant role.